Bright and slip-proof engineered cementitious composites with visible light activated photo-catalysis property for pavement in tunnels - Bawono, Ali Aryo (2022)
Pavement in tunnels requires specific properties and functions. In this study, bright and slip-proof Engineered Cementitious Composites (ECCs) with visible light activated photo-catalysis properties are developed for pavement applications in tunnels. A carbon-modified TiO2 is used to engage a visible light activated photo-catalysis property while white fine aggregates are included to enhance the skid resistance. With 20% silica sand and 5% TiO2 inclusion, the resulting white ECCs possess excellent mechanical properties (i.e., compressive strength > 50 MPa, tensile strength > 4.5 MPa, and tensile strain capacity > 4%) and high skid resistance around 80 BPN, and has high surface reflectivity with a lightness value of 90. Furthermore, the resulting ECCs show strong visible light activated photo-catalysis property with 90% reflectance recovery after 4 h visible light irradiation and only 8% lightness reduction after the accelerated dirt pick-up resistance test.